Comparing phototoxicity during the development of a zebrafish craniofacial bone using confocal and light sheet fluorescence microscopy techniques - Jemielita, Matthew (2012)
The combination of genetically encoded fluorescent proteins and three-dimensional imaging enables cell-type-specific studies of embryogenesis. Light sheet microscopy, in which fluorescence excitation is provided by a plane of laser light, is an appealing approach to live imaging due to its high speed and efficient use of photons. While the advantages of rapid imaging are apparent from recent work, the importance of low light levels to studies of development is not well established. We examine the zebrafish opercle, a craniofacial bone that exhibits pronounced shape changes at early developmental stages, using both spinning disk confocal and light sheet microscopies of fluorescent osteoblast cells. We find normal and aberrant opercle morphologies for specimens imaged with short time intervals using light sheet and spinning disk confocal microscopies, respectively, under equivalent exposure conditions over developmentally-relevant time scales. Quantification of shapes reveals that the differently imaged specimens travel along distinct trajectories in morphological space. (A) Schematic: Light sheet microscopy of zebrafish embryos. Opercle-forming osteoblasts following twenty-four hours of (B) light sheet imaging, showing normal growth, and (C) spinning disk confocal imaging, showing aberrant growth.